Pengaruh Usaha Mikro Kecil dan Menegah (UMKM) dan Tenaga Kerja Terhadap Produk Domestik Bruto (PDB) di Indonesia - Asri A; Aslan A; Nurus Soimah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
UMKM actors seem very important to increase per capita income or improve the economy of a region. UMKM players are required to be able to participate in developing the country's economy and compete globally in economic integration activities between ASEAN countries. The main data in this study used secondary data from the Central Bureau of Statistics, Kemenkop and UMKM as well as various other sources and literature studies related to this research. The dependent variable in this study is Indonesia's Gross Domestic Product (GDP), the independent variable used is the variable number of UMKMs and the number of UMKM workers. The purpose of this study was to analyze the effect of the number of UMKMs and the number of UMKM workers on the Indonesian economy (GDP). From the research results, it is known that the number of UMKMs and the number of workers is a significant influence on the GDP variable. In total the UMKM sector can influence Indonesia's economic development.